SUMATRAN HORNBILL AS AN IDEA FOR CREATING PAINTINGS - Lalang Cakra Buana; Muslim Muslim; Azmi Azmi; Khaerul Saleh; Nelson Tarigan; Tifan Muhammad Amirulloh; Sugito Sugito (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
The creation of this work is driven by the author’s profound interest in hornbills, particularly given the alarming rate of their extinction. The author’s objective is to convey the aesthetic significance of this animal to the broader community. The Sumatran hornbill, with its distinctive and striking characteristics, including its large beak, robust claws, and vibrant plumage, serves as the subject matter for this study. Through the meticulous application of acrylic paint on canvas, the author has crafted twelve paintings that meticulously capture the physical attributes of the bird and its natural habitat. Furthermore, these paintings depict the hornbill’s omnivorous lifestyle. The author employs a combination of three distinct techniques: plaque, chiaroscuro, and bravura. These techniques work synergistically to create a dynamic, contrasting, and vivacious portrayal of the hornbill within the paintings. The resulting twelve paintings, each bearing a unique title that reflects the author’s interpretation of the hornbill, provide an in-depth understanding of its physical characteristics, habitat, and behavior. Additionally, these works contribute to the advancement of the art form through the author’s unique perspective and creative expression.